2013
DOI: 10.1097/jac.0b013e31829702f9
|View full text |Cite
|
Sign up to set email alerts
|

Internet Access and Patient Portal Readiness Among Patients in a Group of Inner-City Safety-Net Practices

Abstract: The use of online personal health records (PHRs) threatens to transform the digital divide to a health care divide among the underserved. Little is known about underserved patients' ability to access online PHRs. We examined these factors among patients within safety-net practices. Among respondents (N = 654), only 12% had no experience of using a computer, and most were interested in using it to communicate with their provider. Age, sex, and race were not associated with interest in PHRs. A majority of patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
1
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 3 publications
3
19
1
2
Order By: Relevance
“…In a recent study that examined underserved patients’ readiness towards patient portal use, Sanders et al found that the majority of the patients did have Internet access and were interested in using a patient portal as a way to manage their care [50]. However, they identified that among those who reported barriers to using the Internet, these were due to interests, know-how, and costs [50]. Because most people have access to computers and the Internet, the challenge of adopting and using these technologies becomes more prevalent, as illustrated in our study.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study that examined underserved patients’ readiness towards patient portal use, Sanders et al found that the majority of the patients did have Internet access and were interested in using a patient portal as a way to manage their care [50]. However, they identified that among those who reported barriers to using the Internet, these were due to interests, know-how, and costs [50]. Because most people have access to computers and the Internet, the challenge of adopting and using these technologies becomes more prevalent, as illustrated in our study.…”
Section: Discussionmentioning
confidence: 99%
“…However, determinants of portal adoption are likely to include patient comfort and proficiency with use of the Internet, experiences with Internet applications, available features, anticipated benefits, provider enthusiasm, patient engagement/activation, health literacy, communication preferences, and trust in the provider and health system (18,28,(33)(34)(35)55,58,62,65,66). By anticipating digital deficiencies in older adults and underserved populations, healthcare organizations can develop onsite and remote training activities to enhance uptake of these new technologies (18,21,(67)(68)(69). Organizations should also consider developing freely available, user-friendly applications that extend access to smartphones early in the rollout period.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies in this area merely concluded that usage among underserved population is low due to lack of Internet access [14] while other studies found that even with sufficient access to Internet, logging into patient portals and using it was significantly lower among minority groups [1,11]. These studies speculated that it could be due to lack of sufficient training, poor health literacy, lack of time and poor e-health literacy.…”
Section: Patient Portal Readiness (Ppr) Among the Underservedmentioning
confidence: 99%
“…Among the underserved, access to Internet have been steadily increasing (Pew reports), however, one study [14] found that current Internet access was the most important predictor of patient portal use. It should also be noted that patient portal usage has been low among the general population as well.…”
Section: Internet Access and The Use Of Internet For Health Informatimentioning
confidence: 99%